Estudio neonatal del crecimiento intrauterino en recién nacidos chilenos de clase media 1978-1987 - Gabriela Juez García; Eduardo Lucero Muller; Patricio Ventura-Junca Tobar; Hernán Gonzalez Lorca; José Luis Tapia Illanes; Augusto Winter Garcés (ARS Medica, 2017)
Sin resumen